An integrated core-based analysis for the characterization of flow, transport and mineralogical parameters of the Heletz pilot CO2 storage site reservoir - Tatomir, Alexandru Bogdan; Halisch, Matthias; Duschl, Florian; Peche, Aaron; Wiegand, Bettina; Schaffer, Mario; Licha, Tobias; Niemi, Auli; Bensabat, Jacob; Sauter, Martin (International Journal of Greenhouse Gas Control, 2016)
Keywords: μ-CT; Tortuosity; Site characterization; Porosity; Core-analysis; Mineralogy; Permeability; Geological CO2 storage; Heletz sandstone

Feathery and network-like filamentous textures as indicators for the re-crystallization of quartz from a metastable silica precursor at the Rusey Fault Zone, Cornwall, UK - Yilmaz, Tim I.; Duschl, Florian; Di Genova, Danilo (Solid Earth, 2016)

Fluid inclusion and microfabric studies on Zechstein carbonates (Ca2) and related fracture mineralizations – New insights on gas migration in the Lower Saxony Basin (Germany) - Duschl, Florian; Van Den Kerkhof, Alfons; Sosa, Graciela; Leiss, Bernd; Wiegand, Bettina; Vollbrecht, Axel; Sauter, Martin (Marine and Petroleum Geology, 2016)
Keywords: Basin evolution; Fluid inclusions; Gas migration; Lower Saxony Basin; Fluorite; Fracture mineralization; Microfabrics; Stassfurt carbonate

Kinetic Interface Sensitive Tracers: Experimental Validation in a Two-Phase Flow Column Experiment. A Proof of Concept - Tatomir, Alexandru; De Vriendt, K.; Zhou, D.; Gao, H.; Duschl, Florian; Sun, F.; Licha, T.; Sauter, Martin (Water Resources Research, 2018)
Keywords: column experiment; fluid-fluid interfacial area; transient flow; kinetic interface sensitive tracers; multiphase flow

Post-Variscan structurally-controlled hydrothermal Zn-Fe-Pb sulfide and F-Ba mineralization in deep-seated Paleozoic units of the North German Basin: A review - Nadoll, Patrick; Sosnicka, Marta; Kraemer, Dennis; Duschl, Florian (Ore Geology Reviews, 2019)
Hydrothermal Zn-Pb-Fe sulfide and F-Ba mineralization occur as open space fillings, veins, and fracture coatings in various parts of the North German Basin in Paleozoic sedimentary rocks and volcanic units at depths of up to four kilometers. We present a petrographic and geochemical (fluid inclusion, mineral and formation water geochemistry) inventory of the mineralized zones and review the basin architecture, evolution, and stratigraphy in order to decipher the timing, extent, fluid pathways, and fluid-rock interactions associated with the ore formation. A particular focus lies on the sediment-hosted Zn-Fe-Pb sulfides in the western part of the North German Basin, the Lower Saxony Basin. Samples from hydrothermal veins from the Pre-Permian basement are also being investigated and compared to the North German Basin-style mineralization to uncover possible genetic links between them. The sediment-hosted sulfide mineralization in the Lower Saxony Basin in the Permian Stassfurt Carbonate unit (Ca2) shares many characteristics that are typical for carbonate-hosted base metal sulfide deposits such as MVT deposits. Petrographic observations, fluid inclusion and isotope data provide evidence that Zn-Fe-Pb sulfides were deposited by highly saline metal-rich basinal brines at temperatures of similar to 160 degrees C. Carbon and oxygen isotope data point toward fluid mixing augmented by structurally-controlled fluid migration during the late Cretaceous basin inversion as the primary ore precipitation mechanism with no magmatic component. In the Altmark-Brandenburg Basin, steeply-dipping F-Ba (calcite, anhydrite, quartz) veinlets in Permo-Carboniferous sandstones and volcanic units are evidence for enhanced post-Variscan structurally-controlled fluid flow. Sulfides are, apart from rare occurrences of chalcopyrite, absent. This is interpreted to reflect the paleogeographic position of the Altmark-Brandenburg Basin (deeper paleogeographic basin position without carbonate aquifers), the lack of reductants, and the predominance of nitrogen-rich fluids as documented by fluid inclusions. Measurements on formation waters from the NGB show geochemical similarities to fluid inclusions in ore and gangue minerals and could represent a potential future exploration tool for hydrothermal ore deposits. This has the potential to aid future research and exploration of deeply covered sediment-hosted deposits and to meet future mineral resources demands.
CRIS-Team WoS Importer:2019-04-09
Keywords: Fluorite; Hydrothermal; Permian; Zn-Fe-Pb sulfides; MVT; North German Basin

Reconstruction of cyclic Mesozoic-Cenozoic stress development in SE Germany using fault-slip and stylolite inversion - Köhler, Saskia; Duschl, Florian; Fazlikhani, Hamed; Köhn, Daniel; Stephan, Tobias; Stollhofen, Harald (Geological Magazine, 2022)
The Franconian Platform of SE Germany and the underlying Permian and Triassic rocks that developed from latest Permian to Triassic time were affected by multiple compressional and extensional events that created a complex fracture, fault and stylolite network. We reconstructed the spatio-temporal variations of post-Triassic palaeostress fields in the Franconian Platform and Triassic strata using fault-slip and tectonic stylolite inversion. Our highly resolved stress inversion enables us to demonstrate a cyclic stress evolution from the stress regime of normal faulting to thrusting, strike-slip and back to normal faulting. Five main stress fields correlating with two stress cycles are determined for Late Jurassic to Cenozoic time. The first cycle consists of: (SF1) an initially NE-SW-directed horizontal extension during Late Jurassic to Early Cretaceous time; (SF2) NNE-SSW-directed horizontal compression with an early set of tectonic stylolites prior to the development of reverse and thrust faults; and (SF3) a strike-slip-dominated setting with (N)NE-(S)SW horizontal compression representing a first relaxation. The second cycle comprises (SF4) NW-SE-directed horizontal extension during Oligocene-Miocene time; and (SF5) a second strike-slip-dominated regime with WNW-ESE to NW-SE horizontal compression during the Alpine shortening, creating the youngest set of tectonic stylolites. In addition, we consider the transitional stages between thrusting and a strike-slip regime as a snapshot in the process of intraplate tectonics.
CRIS-Team WoS Importer:2022-08-26

REY and Trace Element Chemistry of Fluorite from Post-Variscan Hydrothermal Veins in Paleozoic Units of the North German Basin - Nadoll, Patrick; Rehm, Meike; Duschl, Florian; Klemd, Reiner; Kraemer, Dennis; Sosnicka, Marta (Geosciences, 2018)
Hydrothermal fluorites from Paleozoic sedimentary rocks and volcanic units in the North German Basin (NGB) have been investigated to create a petrographic and geochemical inventory—with particular focus on strategic elements such as rare earth elements (REE)—and to uncover possible links between the post-Variscan hydrothermal mineralization in the NGB and bordering areas such as the Harz Mountains and Flechtingen Calvörde Block (FCB). Fluorites from ten localities underwent a detailed petrographic examination, including SEM-BSE/CL imagery, and were compositionally analysed using LA-ICP-MS. Overall, REY concentrations are comparatively low in fluorite from all investigated areas—the median sum of REY ranges from 0.3 to 176 ppm. EuropiumCN anomalies are slightly negative or absent, indicating that either the formation fluid experienced temperatures above 250 °C or that fluid-rock interactions and REE enrichment was likely controlled by the source rock (i.e., volcanic) composition and complexation processes. Fluorites from the Altmark-Brandenburg Basin (ABB) and the Lower Saxony Basin (LSB) display distinctly different REYCN signatures, suggesting that fluid compositions and genetic processes such as fluid-rock interaction differed significantly between the two areas. Complex growth zones and REYCN signatures in fluorite from the ABB and the FCB reflect geochemical variability due to adsorption processes and intrinsic crystallographic controls and imply that they are genetically related. Two petrographically and geochemically distinct generations are observed: Fluorite I—light SEM shades, relatively enriched in LREE; Fluorite II—darker SEM shades, comparatively depleted LREE, slightly higher HREE concentrations. These fluorite generations represent zoned (or cyclical) growth within a single progressive hydrothermal event and do not reflect a secondary remobilization process. We demonstrate that increasing Tb/La ratios and decreasing La/Ho ratios can be the result of continuous zoned growth during a single mineralizing event, with significant compositional variations on a micron-scale. This has implications for the interpretation of such trends and hence the inferred genetic evolution of fluorite that displays such geochemical patterns. The complex micro-scale intergrowth of these generations stresses the need for detailed petrographic investigations when geochemical data are collected and interpreted for mineral exploration.<br
Keywords: Remobilization; Trace elements; North German Basin; Rare earth elements; Zoned growth; Hydrothermal veins; Fluorite